Exploring the Potential of Halotolerant Actinomycetes from Rann of Kutch, India: A Study on the Synthesis, Characterization, and Biomedical Applications of Silver Nanoparticles - Paras Dayma; Nisha Choudhary; Daoud Ali; Saud Alarifi; Pravin Dudhagara; Kuldeep Luhana; Virendra Kumar Yadav; Ashish Patel; Rajesh Patel (MDPI AG, 2024)
A tremendous increase in the green synthesis of metallic nanoparticles has been noticed in the last decades, which is due to their unique properties at the nano dimension. The present research work deals with synthesis mediated by the actinomycete Streptomyces tendae of silver nanoparticles (AgNPs), isolated from Little and Greater Rann of Kutch, India. The confirmation of the formation of AgNPs by the actinomycetes was carried out by using a UV-Vis spectrophotometer where an absorbance peak was obtained at 420 nm. The X-ray diffraction pattern demonstrated five characteristic diffraction peaks indexed at the lattice plane (111), (200), (231), (222), and (220). Fourier transform infrared showed typical bands at 531 to 1635, 2111, and 3328 cm−1. Scanning electron microscopy shows that the spherical-shaped AgNPs particles have diameters in the range of 40 to 90 nm. The particle size analysis displayed the mean particle size of AgNPs in aqueous medium, which was about 55 nm (±27 nm), bearing a negative charge on their surfaces. The potential of the S. tendae-mediated synthesized AgNPs was evaluated for their antimicrobial, anti-methicillin-resistant Staphylococcus aureus (MRSA), anti-biofilm, and anti-oxidant activity. The maximum inhibitory effect was observed against Pseudomonas aeruginosa at (8 µg/mL), followed by Escherichia coli and Aspergillus niger at (32 µg/mL), and against Candida albicans (64 µg/mL), whereas Bacillus subtilis (128 µg/mL) and Staphylococcus aureus (256 µg/mL) were much less sensitive to AgNPs. The biosynthesized AgNPs displayed activity against MRSA, and the free radical scavenging activity was observed with an increase in the dosage of AgNPs from 25 to 200 µg/mL. AgNPs in combination with ampicillin displayed inhibition of the development of biofilm in Pseudomonas aeruginosa and Streptococcus pneumoniae at 98% and 83%, respectively. AgNPs were also successfully coated on the surface of cotton to prepare antimicrobial surgical cotton, which demonstrated inhibitory action against Bacillus subtilis (15 mm) and Escherichia coli (12 mm). The present research integrates microbiology, nanotechnology, and biomedical science to formulate environmentally friendly antimicrobial materials using halotolerant actinomycetes, evolving green nanotechnology in the biomedical field. Moreover, this study broadens the understanding of halotolerant actinomycetes and their potential and opens possibilities for formulating new antimicrobial products and therapies.